Structural control of nanoporous frameworks consisting of minimally stacked graphene walls - Pirabul, Kritin; Pan, Zheng-Ze; Nishihara, Hirotomo (Frontiers in Materials, 2024)
This mini-review provides an in-depth analysis of the formation and post-processing of nanoporous graphene materials via methane chemical vapor deposition (CH4-CVD) using nanostructured metal oxide templates, including Al2O3, MgO, and SiO2. Initially, the formation of graphene sheets is discussed in terms of the role of CH4-CVD, the influence of templates, and the underlying mechanism for tailoring the structures of the graphene materials. Following this, the discussion extends to the postgraphene formation process. We will focus on key steps, including template removal and graphene repair via zipping reactions at high temperatures. Additionally, we will evaluate the conditions to prevent undesired structural transformations. The correlation between the structural features and transformations occurring during post-processing is also examined. The materials fabricated through these methods exhibit impressive properties of high porosity, minimal edge sites, superior oxidation resistance, and elasticity, positioning them as promising materials for applications in various applications.Graphene, an allotrope of carbon, appears as a monolayer consisting of sp 2 hybridized carbon atoms arranged in a hexagonal lattice configuration. Due to its monolayer structure, it presents an extraordinarily high theoretical specific surface area of approximately 2627 m 2 g -1 .(Siqueira and